Analysis of the effectiveness and efficiency of village fund management in Padaloang Village, Dua Pitue Sub-District, Sidenreng Rappang Regency - Kurniawan; Fadlina; Iqbal, Muhammad (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: This study aims to identify and analyze the level of effectiveness and efficiency of village funds from 2020 to 2022 in Padaloang Village, Dua Pitue Sub-District, Sidenreng Rappang Regency. Methods: The research method used is qualitative with a narrative approach. The data sources used are secondary data, which were analyzed using the effectiveness and efficiency ratios, and primary data in the form of interview results, which were analyzed using effectiveness and efficiency measurements. Findings: The study results show that the analysis of the effectiveness of village fund management in Padaloang Village from 2020 to 2022 indicates stable development. Each year, the average village fund management level reaches 96%. Conclusion: This indicates that the financial management of Padaloang Village is considered effective, with the calculation results exceeding 90% and the interview results also aligning with the effectiveness measurements used. Novelty/Originality of this article: The efficiency analysis shows that the management of village funds in Padaloang Village experienced a decline during the 2020—2022 period. The average efficiency level of Padaloang Village's financial management during this period was 97,80%, indicating less efficiency because the value is less than 100%, but the interview results show alignment with the efficiency measurements used. These results indicate that the village government still uses its budget less efficiently but effectively. This shows that the objectives can be achieved but with relatively high resources.